Degradation of Archaeological Remains by Shipworm. (2nd July 2016) - Eriksen, Anne Marie; Gregory, David
Abstract : The marine borer, known as shipworm, has long been known for their degradation of wooden constructions in the marine environment. This review presents the results from a variety of experiments conducted at the National Museum of Denmark throughout the past five years dealing with the in situ preservation of maritime archaeological artefacts in light of the threat from shipworm. The aim of the research has been to improve methods and analyses for conducting experiments with shipworm, and to better our understanding of their attack pattern and how to stop an active attack in situ .